Innovation capability and risk attitude mediate the effects of knowledge management and financial literacy on MSME performance - Meldona,; Soetjipto, Budi Eko; Wardoyo, Cipto; Hermawan, Agus; Utaberta, Nangkula (Journal of Social Economics Research, 2023)
Halal micro, small and medium enterprises (MSMEs) play an important role in the economy, supporting the rapid development of the world's halal industry. The performance of halal MSMEs is influenced by knowledge management and financial literacy. Based on knowledge-based theory, which focuses on internal factors to explain business strategies, innovation capabilities and risk attitudes can mediate the influence of knowledge management and financial literacy on the performance of halal MSMEs. Data collected using quantitative proximity from a sample of 195 owners of halal MSMEs in Malang Raya, Indonesia, was analyzed using structural equation modeling (SEM). The findings showed that knowledge management and financial literacy affect the performance of MSMEs. The innovation ability and risk attitude of MSME owners mediate the effects of knowledge management and financial literacy on the performance of MSMEs. When knowledge is managed effectively, it creates unique capabilities that contribute to improved performance through innovation, realized through innovative products, and risk attitude, realized through optimized opportunities.